Flying into the hurricane: law, policy and practice implications of cloud computing. (1st January 2012) - Clark, Eugene; Sims, Ian M.
The 1960s was the era of mainframe computing and the 1970s the era of mini-computing and business logic applications. The 1980s ushered in client/server computing and the 1990s desktop computing. In the early 2000s, we are experiencing the age of cloud computing. This article defines and outlines the advantages and models of cloud computing in its various forms. It surveys the legal risks inherent in this form of computing and suggests ways in which these risks can best be managed. Finally, the article suggests avenues for future investigation and reform so that the storms may be avoided and the promised silver linings achieved.